School Well-Being as an Integrative Biopsychosocial Model: A Decade of Bibliometric and Science Mapping Analysis - Hafizh Zain Abdillah; Anniez Rachmawati Musslifah; Faqih Purnomosidi (ASANKA : Journal of Social Science and Education, 2026)
School well-being is increasingly recognized as a biopsychosocial construct that bridges welfare and subjective well-being theories. However, the field lacks a comprehensive account of its publication trends, intellectual structure, and thematic evolution. This study offers the first decade-spanning bibliometric synthesis of Scopus-indexed school well-being research (2017-2026), screened via PRISMA 2020 to yield 110 eligible articles, analyzed using Biblioshiny (Bibliometrix R package) and VOSviewer for complementary performance analysis and science mapping. Results show scientific production remained stagnant before 2020, rose after the COVID-19 pandemic, consolidated between 2021 and 2023, and reached record output in 2025. Productivity was concentrated among a few author clusters and institutions across Nordic, Western European, and Anglophone research ecosystems, as evidenced by steep Lotka's Law scattering (Beta = 3.51) and a Bradford's Law core of 11 journals. The field's intellectual structure integrates welfare theory, ecological systems theory, subjective well-being theory, and self-determination theory, with thematic evolution shifting toward psychometric validation, gender-differentiated analysis, and bullying-related research. Convergent evidence from keyword co-occurrence and thematic evolution analysis shows sociologically and psychologically oriented clusters increasingly interlinked around the core "school well-being" node, indicating the field is coalescing into an integrative biopsychosocial model, offering a foundation for future theoretical refinement, instrument validation, and evidence-based policy.